Impact of audit committee on organizational performance of listed hotels and travels in Sri Lanka - Balagobei, S.; Velnampy, T. (Macrothink Institute, 2018)
The audit committee is one of the key elements in the corporate governance structure that helps to control and monitor management in the organization. The aim of this study is to investigate the impact of audit committee on organizational performance of listed hotels and travels in Sri Lanka. The sample consists of 15 listed hotels and travels in Sri Lanka. In this study, data was collected from secondary sources and hypotheses are examined by using Pearson’s correlation and multiple regression analysis (Eviews). The results reveal that audit committee attributes such as AC independence, AC experts and AC meetings have a significant impact on organizational performance of listed hotels and travels in Sri Lanka. Further audit committee size is not found to have a significant impact on the organizational performance. The findings could be useful to regulators in other jurisdiction who are looking at ways to enhance the effectiveness of AC, overall firm governance and enhance the organizational performance.
Keywords: Audit Committee; Organizational performance; Audit committee independence; Audit committee experts; Audit committee meetings